Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1977
DOI: 10.1042/cs0520351
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Selected Endocrine Organ Ablation to Modify the Natriuresis of Blood Volume Expansion in the Dog

Abstract: 1. Selected organ-ablation experiments were performed in dogs in an attempt to identify the source of the natriuretic hormone postulated to participate in the natriuresis of blood volume expansion. 2. An isolated dog kidney perfused with blood from the femoral artery of deoxycorticosterone-loaded dogs subjected to acute volume expansion with equilibrated blood served as the bioassay system for the natriuretic factor. Four groups were studied after the following procedures: group I, no ablation; group II, thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Moreover, because the perfusion dog was preloaded with deoxycorticosterone and received a continuous infusion ofvasopressin, decreases in the circulating levels of these hormones were excluded also as possible factors that influence the natriuretic response. These observations confirm our previous studies (3)(4)(5) and are consistent with the hypothesis that the increased sodium excretion from the isolated kidney is mediated by a humoral factor activated by expansion of the dog's blood volume.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Moreover, because the perfusion dog was preloaded with deoxycorticosterone and received a continuous infusion ofvasopressin, decreases in the circulating levels of these hormones were excluded also as possible factors that influence the natriuretic response. These observations confirm our previous studies (3)(4)(5) and are consistent with the hypothesis that the increased sodium excretion from the isolated kidney is mediated by a humoral factor activated by expansion of the dog's blood volume.…”
Section: Discussionsupporting
confidence: 81%
“…Studies in our laboratory also support the hypothesis that a humoral mechanism, unrelated to mineralocorticosteroid or vasopressin, participates in the natriuretic response elicited by expansion of the blood volume (3)(4)(5). We have used a cross-circulation technique involving an isolated dog kidney connected to the circulation of an intact dog and have observed that infusing equilibrated blood into the dog promotes a significant increase in sodium excretion in the isolated kidney.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…However, no evidence has been available to support the presence of ouabain in the anterior pituitary. 13 In contrast, we have recently shown the presence of immunoreactive ouabain in the hypothalamus, 14 suggesting a hypothalamic origin of endogenous ouabain. 15 It is not known, however, whether the hypothalamic ouabain is released into the circulation, and if so, how the pituitary tumor affects the hypothalamic ouabain.…”
Section: Discussionmentioning
confidence: 91%